1994
DOI: 10.1007/bf01418234
|View full text |Cite
|
Sign up to set email alerts
|

Private ownership form and productive efficiency: Electric cooperatives versus investor-owned utilities

Abstract: Property rights theory predicts that private firms whose ownership shares am not tradable will not be managed efficiently. This paper tests that theory by comparing the costs of rural electric cooperatives (RECs) and investor-owned electric utilities (lOUs). Separate translog cost functions are estimated for the REGs and the IOUs. The estimated costs of producing several three-product output bundles are then compared across ownership form under the assumption that all firms face identical input prices. The emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…In addition, the cooperative system increases the individual costs of oversight, because of the absence of a secondary market to sell the company shares, which makes it relatively more costly for each individual owner to assess the performance of management (Berry, 1994). This ownership structure also minimizes any incentive for the individual principal to monitor the firm's performance as her returns to monitoring are primarily based on a potential difference in the present value of the costs of the goods and services she purchases from the firm in perpetuity, a value that is difficult to calculate or monetize ex ante.…”
Section: Cooperative Organizations and Investor-owned Firm Efficienciesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the cooperative system increases the individual costs of oversight, because of the absence of a secondary market to sell the company shares, which makes it relatively more costly for each individual owner to assess the performance of management (Berry, 1994). This ownership structure also minimizes any incentive for the individual principal to monitor the firm's performance as her returns to monitoring are primarily based on a potential difference in the present value of the costs of the goods and services she purchases from the firm in perpetuity, a value that is difficult to calculate or monetize ex ante.…”
Section: Cooperative Organizations and Investor-owned Firm Efficienciesmentioning
confidence: 99%
“…This, coupled with the weak governance system surrounding the cooperative, makes these firms more prone to serve the interests of the entrenched principals. As a consequence of these magnified principal-principal issues, numerous studies have demonstrated that cooperative companies tend to become less efficient than their investor-owned counterparts in developed countries (Berry, 1994;Verbrugge and Jahera, 1981), a pattern that is likely to be manifest to a worse degree in developing countries: H1. The cooperative firm will have a lower level of firm efficiency than the investor-owned firm in an emerging market.…”
Section: Cooperative Organizations and Investor-owned Firm Efficienciesmentioning
confidence: 99%
“…Most comparative efficiency studies have found that cooperatives are less efficient than private firms. Porter and Scully (1987), Ferrier and Porter (1991), and Berry (1994) argued that U.S. cooperatives exhibited technical and scale inefficiencies because their stocks were not tradable and individual members had limited incentives to monitor the cooperative's performance. Akridge and Hertel (1992), however, found that cooperatives were no less efficient than investor‐owned firms.…”
Section: Prior Researchmentioning
confidence: 99%
“…Rose and Joskow (1990) privately owned counterparts. Berry (1994) finds that investor owned electric companies are more technically efficient than are rural electric cooperatives, which are owned by their customers. Kwoka (2006) finds that privately owned electricity distribution companies are less technically efficient than their publically owned counterparts unless faced with either competition for large customers or benchmark competition.…”
Section: Electricitymentioning
confidence: 99%